2022
DOI: 10.1177/22338659221120056
|View full text |Cite
|
Sign up to set email alerts
|

Testing the environmental Kuznets curve hypothesis in Africa: A focus on the moderating effect of Sino-African economic cooperation

Abstract: This study tested whether the Sino-African economic partnership, represented by the share of Chinese foreign direct investment (FDI), affected the validity of the environmental Kuznets curve (EKC) hypothesis in Africa. Therefore, we zeroed in on 41 countries and ran a panel analysis, covering the period ranging from 2003 to 2018, to examine whether the effect of gross domestic product (GDP) per capita on carbon dioxide (CO2) and methane (CH4) emissions per capita was moderated by the share of Chinese FDI stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Some countries often get more inflow of FDI even with their stringent environmental regulations. Elekeleme and Hong (2023) market orientation was expanding from coastal zones to the whole of China, the regional development and FDI's impact on CO 2 emission also showed an uneven nature. The researchers concluded that eastern area provinces typically showed lower CO 2 emissions from FDI and higher market development, whereas four western area provinces displayed higher CO 2 emissions from FDI and lower market development.…”
Section: Foreign Direct Investment-environmental Quality Nexusmentioning
confidence: 99%
“…Some countries often get more inflow of FDI even with their stringent environmental regulations. Elekeleme and Hong (2023) market orientation was expanding from coastal zones to the whole of China, the regional development and FDI's impact on CO 2 emission also showed an uneven nature. The researchers concluded that eastern area provinces typically showed lower CO 2 emissions from FDI and higher market development, whereas four western area provinces displayed higher CO 2 emissions from FDI and lower market development.…”
Section: Foreign Direct Investment-environmental Quality Nexusmentioning
confidence: 99%